Comparison of Outcomes Between Transperitoneal and Retroperitoneal Robotic Partial Nephrectomy: A Meta-Analysis Based on Comparative Studies - Zhu, Daqing; Shao, Xue; Guo, Gang; Zhang, Nandong; Shi, Taoping; Wang, Yi; Gu, Liangyou (Frontiers in Oncology, 2021)
Background: To compare perioperative, functional and oncological outcomes between transperitoneal robotic partial nephrectomy (TRPN) and retroperitoneal robotic partial nephrectomy (RRPN). Methods: A literature searching of Pubmed, Embase, Cochrane Library and Web of Science was performed in August, 2020. Pooled odds ratios (ORs) or weighted mean differences (WMDs) with 95% conﬁdence intervals (CIs) were estimated using ﬁxed-effect or random-effect model. Publication bias was evaluated with funnel plots. Only comparative studies with matched design or similar baseline characteristics were included. Results: Eleven studies embracing 2984 patients were included. There was no signiﬁcant difference between the two groups regarding conversion to open (P = 0.44) or radical (P = 0.31) surgery, all complications (P = 0.06), major complications (P = 0.07), warm ischemia time (P = 0.73), positive surgical margin (P = 0.87), decline in eGFR (P = 0.42), CKD upstaging (P = 0.72), and total recurrence (P = 0.66). Patients undergoing TRPN had a significant higher minor complications (P = 0.04; OR: 1.39; 95% CI, 1.01-1.91), longer operative time (P < 0.001; WMD: 21.68; 95% CI, 11.61 to 31.76), more estimated blood loss (EBL, P = 0.002; WMD: 40.94; 95% CI, 14.87 to 67.01), longer length of hospital stay (LOS, P < 0.001; WMD: 0.86; 95% CI, 0.35 to 1.37). No obvious publication bias was identified. Conclusion: RRPN is more favorable than TRPN in terms of less minor complications, shorter operative time, less EBL, and shorter LOS. Methodological limitations of the included studies should be considered while interpreting these results.